1993
DOI: 10.1037/0012-1649.29.2.389
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive readiness and adolescent parenting.

Abstract: This study compared cognitive readiness for parenting in 171 pregnant adolescents, 48 nonpregnant adolescents, and 38 pregnant adults. The relations between cognitive readiness and parenting stress and behavior were also assessed. Results indicated that adolescents were less cognitiveiy prepared, experienced more stress in the parenting role, and were less adaptive in their parenting style than adult mothers. Finally, relations between cognitive readiness and parenting stress and maternal interactional style w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
0
11

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 30 publications
3
93
0
11
Order By: Relevance
“…Participants in this study included a subsample of mother-child dyads (N ¼ 70) drawn from the Notre Dame Adolescent Parenting Project, a longitudinal study following, first-time adolescent mothers and their children from the last trimester of pregnancy through children's adolescence (Borkowski et al, 2007;Sommer et al, 1993;Whitman et al, 2001). Teenage mothers were recruited from school-age mothers programs, hospital clinics, and social service agencies in South Bend, IN or Aiken, SC.…”
Section: Methods Participantsmentioning
confidence: 99%
“…Participants in this study included a subsample of mother-child dyads (N ¼ 70) drawn from the Notre Dame Adolescent Parenting Project, a longitudinal study following, first-time adolescent mothers and their children from the last trimester of pregnancy through children's adolescence (Borkowski et al, 2007;Sommer et al, 1993;Whitman et al, 2001). Teenage mothers were recruited from school-age mothers programs, hospital clinics, and social service agencies in South Bend, IN or Aiken, SC.…”
Section: Methods Participantsmentioning
confidence: 99%
“…For example, maternal 'cognitive readiness' for parenting (defined as knowledge of child development, parenting style preferences and parenting attitudes) has been found to directly impact a child's tendency to have behavioural problems (43). Despite this, it has been suggested that maternal age and education level may not directly cause children's behavioural problems, as the disadvantage of children born to younger mothers has been shown to be reduced when the effects of maternal family background are controlled (44). Although measures of maternal family background were not explicitly collected in this study, the association between young maternal age and limited education on preschool behavioural difficulties remained, after controlling for a number of factors related to family socio-demography.…”
Section: /36mentioning
confidence: 99%
“…Elles ont aussi un réseau social plus limité (Buchholz et KornBursztyn, 1993). Or, certaines études contrôlées statistiquement pour le statut socioéconomique, ont montré qu'il n'y avait pas de différences sur le plan parental entre les mères adolescentes et les mères adultes (Garcia Coll et al, 1987 ;Sommer et al, 1993). Par contre, d'autres études utilisant des groupes comparables sur le plan socioéconomique ont rapporté des différences entre les deux groupes de mères, mais moindres que ce qui était attendu (Benasich et Brooks-Gunn, 1996 ;Chase-Lansdale et al, 1994 ;Wakschlag et al, 1996).…”
Section: Prévalence Et Cooccurrence De Cinq Formes De Maltraitance Enunclassified